2017
DOI: 10.1038/s41598-017-04428-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel pH-sensitive carrier for the delivery of antitumor drugs: histidine-modified auricularia auricular polysaccharide nano-micelles

Abstract: The study was aimed to design a novel pH-sensitive carrier to deliver antitumor drugs to increase treatment efficiency. Histidine (His)was used to modify auricularia auricular polysaccharide (AAP) by esterification. Proton nuclear magnetic resonance spectrometry was developed to characterize the His-AAP carrier and the His-AAP Paclitaxel (PTX) micelles were prepared by self-assembled organic solvent evaporation. The formation of His-AAP PTX micelles was confirmed by dynamic light-scattering, transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 42 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…The simplest way to develop micelles containing histidine is to attach hydrophobic histidine to hydrophilic macromolecules, such as hyaluronic acid ( Wu et al, 2016 ), dextran ( Yin et al, 2020 ), and auricularia auricular polysaccharide (AAP) ( Wang et al, 2017 ). In the above micelles, histidine is usually used as a micellar core.…”
Section: Histidine-based Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest way to develop micelles containing histidine is to attach hydrophobic histidine to hydrophilic macromolecules, such as hyaluronic acid ( Wu et al, 2016 ), dextran ( Yin et al, 2020 ), and auricularia auricular polysaccharide (AAP) ( Wang et al, 2017 ). In the above micelles, histidine is usually used as a micellar core.…”
Section: Histidine-based Micellesmentioning
confidence: 99%
“…Next, paclitaxel was loaded into His-AAP micelles. Compared to that at pH 7.4, the paclitaxel accumulated release rate was increased by about 18% for 12 h at pH 5.0 ( Wang et al, 2017 ). Research by Chang et al (2010) also confirmed that micelles based on histidine had the characteristic of pH-sensitive drug release.…”
Section: Histidine-based Micellesmentioning
confidence: 99%
“…A. auricular lacks cholesterol and is relatively rich in polysaccharides, minerals, and protein (Zheng et al, ). This mushroom has been shown to prevent thrombosis (Fan et al, ), tumors (Ma, Wang, Zhang, Zhang, & Ding, ), and to reduce cytotoxicity (Wang et al, ) and oxidative damage (Oke & Aslim, ) and to have an antiradiation effect (Xun et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Trigger by pH is one of the well-explored internal stimuli, especially in the drug delivery eld. 11,12 For the intracellular delivery of therapeutics, upon endocytosis, cargoes and carriers usually experience a pH drop during intracellular trafficking, from neutral ($pH 7.4) extracellular environment to slightly acidic ($pH 6.5) in early endosome, then more acidic ($pH 5.5) late endosome and nally lysosome ($pH 4.5).…”
Section: Introductionmentioning
confidence: 99%
“…11,14 Ultrasound is one of the noninvasive external stimuli, which is able to enhance/disrupt or recongure the peptide self-assemblies through adjustable mechanical perturbation. For example, short brils of 20-100 nm could be generated through ultra-sonication of mature brils, 15 which is a routine method to make self-assembly seeds.…”
Section: Introductionmentioning
confidence: 99%